Is everybody human? The relationship between humanity and animality in Western and Amerindian myth narratives. (September 2019) - Kawaguchi, Douglas; Guimarães, Danilo S
The general problem this research approaches is the observation that, in Western cultures, Human occupies a central place and is identified with the cosmological wholeness—a worldview which is in tune with the paradigm of massive abuses that are practiced against animals who 1 are exploited by industry worldwide and with the environmental catastrophe we witness nowadays. Departing from that problem, this paper presents and discusses the Western notion indicated above, comparing it with the notion of Yanomami indigenous people about human's place in the universe. We use a dialogical methodology pertinent to semiotic-cultural constructivism in psychology, focusing on the relationship between "human" and non-human animal in the two mentioned cultures, through the analysis of two creation myths : The Book of Genesis, the first book of the Hebrew-Christian Bible; and The Falling Sky: Words from a Yanomami Shaman, a set of narratives from indigenous leader Davi Kopenawa. Results show that Western and Amerindian narratives present mostly opposite conceptions concerning the relationships between "humanity" and animality and that meanings for "human" and "animal" differ essentially in both. From the tension with Amerindian cosmology and its relationship with nonhuman animal, we call into question the ethno-anthropocentrism that is present in Western psychology since its birth. Given that psychology lays its foundations on a worldview that presupposes a strict split between nature and Humanity (assuming, e.g. an insurmountable incompatibility between the impulse of our "natural" desires and the regulation and prohibitions imposed by "culture"), this research intends to draw attention to the fact that the naturalist ontology is not an a priori nor a necessary condition for the construction of self-identity in the world. Whereas this presupposed Human "alienation" from nature remains taken for granted in the hegemonic theoretical–methodological reflections in psychology, we discuss the limits of Eurocentered psychology research and its implications in a dialogical epistemology.